Market Added Value, Profitability, Inflation, and Company Size on Transportation Company Share Prices - Effendi, Askhabi Nur; Dewi, Nurma Gupita (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2024)
Purpose: Share price is a measure of investor interest in the decision to invest in a company. The aim of this research is to show the influence of market value, profitability, inflation and company size on stock prices. Method: This research uses a quantitative descriptive approach. Secondary data is information used in research, where the information is obtained from the database of transportation companies registered on the IDX within a three year period, namely 2020-2022. So far 16 transportation companies have been selected as research samples using the purposive sampling method. The research data analysis method uses multiple linear regression analysis using SPSS version 26. Results: The research results show that Market Value Added and company size have a significant positive effect on stock prices, while profitability and inflation have a negative and insignificant effect on stock prices. Implications: The research can be used as evaluation and review material for companies regarding the performance of ups and downs in share prices. In addition, future corporate performance and responsibility are expected to increase in connection with the evaluation of the corporate governance system. Novelty: The novelty of this research is that it does not only focus on internal factors that influence company share prices but also external factors, namely inflation. Apart from that, this research examines transportation companies using the latest data, namely 2020-2022.